Genetic variation (CHRNA5), medication (combination nicotine replacement therapy vs. varenicline), and smoking cessation. (1st September 2015) - Chen, Li-Shiun; Baker, Timothy B.; Jorenby, Douglas; Piper, Megan; Saccone, Nancy; Johnson, Eric; Breslau, Naomi; Hatsukami, Dorothy; Carney, Robert M.; Bierut, Laura J.
Highlights: Comparisons of smoking cessation trials demonstrate inconsistent genetic results. A placebo control arm is important to determine the pharmacogenetic effect. Individuals with risk genotypes have difficulty quitting smoking without treatment. This increased risk may be ameliorated by effective pharmacological treatment. Abstract: Objective : Recent evidence suggests that the efficacy of smoking cessation pharmacotherapy can vary across patients based on their genotypes. This study tests whether the coding variant rs16969968 in the CHRNA5 nicotinic receptor gene predicts the effects of combination nicotine replacement therapy (cNRT) and varenicline on treatment outcomes. Method : In two randomized smoking cessation trials comparing cNRT vs. placebo, and varenicline vs. placebo, we used logistic regression to model associations between CHRNA5 rs16969968 and abstinence at end of treatment. Results : For abstinence at end of treatment, there was an interaction between cNRT and rs16969968 ( X 2 = 8.15, d f = 2, omnibus- p = 0.017 for the interaction); individuals with the high-risk AA genotype were more likely to benefit from cNRT. In contrast, varenicline increased abstinence, but its effect did not vary with CHRNA5 . However, the genetic effects differed between the placebo control groups across two trials (wald = 3.94, d f = 1, p = 0.047), this non-replication can alter the interpretation of pharmacogenetic findings. Conclusions : Results from two complementary smoking cessation trials demonstrate inconsistent genetic results in the placebo arms. This evidence highlights the need to compare the most effective pharmacotherapies with the same placebo control to establish pharmacogenetic evidence to aid decisions on medication choice for patients trying to quit smoking.